Preptin promotes proliferation and osteogenesis of MC3T3‐E1 cells by upregulating β‐catenin expression. Issue 7 (6th February 2019) - Xiao, Chunyuan; Li, Wei; Lu, Tianlin; Wang, Jiayi; Han, Jie
Abstract: Preptin, an oligopeptide secreted by pancreatic β‐cell, plays a significant role in glycometabolism and bone metabolism. Preptin strengthens proliferation and differentiation of osteoblasts, but the mechanism is unclear. Here, we explored the role of the Wnt/β‐catenin signaling pathway which is well known to affect bone development and remodelling in the function of preptin. We found that preptin promoted the cell proliferative activity and osteoblastic differentiation in osteoblast‐like MC3T3‐E1 cells in a dose‐independent manner, as evidenced by elevation in osteogenic genes, alkaline phosphatase activity and alizarin red staining in a dose‐independent manner. Additionally, our findings demonstrated that the β‐catenin expression level and runt‐related transcription factor 2, which is the key downstream target of this pathway, were increased. The Wnt/β‐catenin signalling pathway antagonist DKK1 abrogated the proliferative effect and differentiation function of preptin in MC3T3‐E1 cells. These data indicated that preptin may be a potential therapeutic target for the treatment of osteoporosis and that osteogenic impact of preptin in MC3T3‐E1 cells might be mediated by the Wnt/β‐catenin signalling pathway. © 2019 IUBMB Life, 9999(9999):1–9, 2019